1979
DOI: 10.1073/pnas.76.5.2359
|View full text |Cite
|
Sign up to set email alerts
|

Darwin's finches: Population variation and sympatric speciation

Abstract: The classical model of the adaptive radiation of Darwin's finches is one of repeated speciation in allopatry. Evidence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 18 publications
1
43
0
Order By: Relevance
“…Strong assortative mating, in turn, could power intermorph reproductive isolation and genetic divergence (Huber et al 2007). A parallel argument had been made previously for the Geospiza conirostris population on Isla Genovesa (Grant & Grant 1979), which in initial years of study showed vocal morphs and some bimodality in morphology. However, initial observed patterns of assortative mating broke down over subsequent years (Grant & Grant 1989).…”
Section: Discrimination Of Sympatric Morphs J Podos 1035mentioning
confidence: 69%
“…Strong assortative mating, in turn, could power intermorph reproductive isolation and genetic divergence (Huber et al 2007). A parallel argument had been made previously for the Geospiza conirostris population on Isla Genovesa (Grant & Grant 1979), which in initial years of study showed vocal morphs and some bimodality in morphology. However, initial observed patterns of assortative mating broke down over subsequent years (Grant & Grant 1989).…”
Section: Discrimination Of Sympatric Morphs J Podos 1035mentioning
confidence: 69%
“…Gill (1973) has stressed the rarity with which avian microgeographic variation occurs on islands. Grenada may be one of the smallest islands with a polymorphic bird species (but see Grant and Grant, 1979). …”
Section: Discussionmentioning
confidence: 99%
“…In one, Grant & Grant (1979) described a population of Geospiza conirostris (large cactus ground finch) on Genovesa Island that was composed of two male types singing different songs and having different beak sizes and foraging habits. These initial distinctions subsequently broke down (Grant & Grant 1989), and no further attention has been directed towards this population.…”
Section: Introductionmentioning
confidence: 99%